Religious Differences in Physical and Mental Health among Israeli Jews: Findings from the Global Flourishing Study - Levin, Jeffrey S. (Journal of religion and health, 2024)
Numerous studies have identified religious correlates of health indicators, but relatively few have been conducted among Jewish populations in Israel or the diaspora. This study investigates the possibility of a religious gradient in physical and mental health and well-being across the familiar categories of Jewish religious identity and observance in Israel: hiloni (secular), masorti lo dati (traditional, non-religious), masorti (traditional), dati (religious or Orthodox), and charedi (ultra-Orthodox). Data are from Jewish respondents aged 18 and over (N = 2916) from the Israeli sample of the new, 22-nation Global Flourishing Study, which used stratified, probability-based sampling and assessed demographic, socioeconomic, political, religious, health-related, and other variables. This analysis investigated religious differences in nine indicators of physical and mental health and well-being among Israeli Jews. Using a strategy of one-way ANOVA and ANCOVA, adjusting for complex sampling design components, a statistically significant "dose-response"-like gradient was found for eight of the outcome measures, validated by additional multiple comparison tests. For four "positively" worded indicators (physical and mental health, happiness, and life satisfaction), scores increased consistently from the hiloni to the charedi categories. For four of five "negatively" worded indicators (bodily pain, depression, anxiety, and suffering), scores decreased across the same categories. Results withstood adjusting for effects of age, sex, education, marital status, urbanicity, income, and nativity (whether born in Israel). Among Israeli Jews, greater religiousness was associated with higher levels of health and well-being and lower levels of somatic and psychological distress.